Comparative Proteomic Study of Fatty Acid-treated Myoblasts Reveals Role of Cox-2 in Palmitate-induced Insulin Resistance - Chen, Xiulan (Sci Rep, 2016)
Accumulated studies demonstrate that saturated fatty acids (FAs) such as palmitic acid (PA) inhibit insulin signaling in skeletal muscle cells and monounsaturated fatty acids such as oleic acid (OA) reverse the effect of PA on insulin signaling. The detailed molecular mechanism of these opposite effects remains elusive. Here we provide a comparative proteomic study of skeletal myoblast cell line C2C12 that were untreated or treated with PA, and PA plus OA. A total of 3437 proteins were quantified using SILAC in this study and 29 proteins fall into the pattern that OA reverses PA effect. Expression of some these proteins were verified using qRT-PCR and Western blot. The most significant change was cyclooxygenase-2 (Cox-2). In addition to whole cell comparative proteomic study, we also compared lipid droplet (LD)-associated proteins and identified that Cox-2 was one of three major altered proteins under the FA treatment. This finding was then confirmed using immunofluorescence. Finally, Cox-2 selective inhibitor, celecoxib protected cells from PA-reduced insulin signaling Akt phosphorylation. Together, these results not only provide a dataset of protein expression change in FA treatment but also suggest that Cox-2 and lipid droplets (LDs) are potential players in PA- and OA-mediated cellular processes.